2018
DOI: 10.1590/0004-282x20180089
|View full text |Cite
|
Sign up to set email alerts
|

Is self-report sleepiness associated with cognitive performance in temporal lobe epilepsy?

Abstract: Sleepiness and cognitive impairment are common symptoms observed in patients with epilepsy. We investigate whether self-reported sleepiness is associated with cognitive performance in patients with refractory mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS). Seventy-one consecutive patients with MTLE-HS were evaluated with the Stanford Sleepiness Scale (SSS) before neuropsychological evaluation. Their mean SSS scores were compared with controls. Each cognitive test was compared between patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the Vascuoto et al [40] study, despite the greater perceived sleepiness of patients with MTLE and hippocampal sclerosis, they did not perform worse on cognitive tests than the control group. According to Chan et al [41], sleep in children with epilepsy enhances learning.…”
Section: Memorymentioning
confidence: 85%
See 3 more Smart Citations
“…In the Vascuoto et al [40] study, despite the greater perceived sleepiness of patients with MTLE and hippocampal sclerosis, they did not perform worse on cognitive tests than the control group. According to Chan et al [41], sleep in children with epilepsy enhances learning.…”
Section: Memorymentioning
confidence: 85%
“…The undoubted limitations of the study were the subjective nature of the SSS test, the language barrier in its performance, and the fact that no alternative test was used that would confirm the obtained results. To sum up, the authors concluded that the sense of sleepiness is not a valuable factor in the case of neuropsychological research [40].…”
Section: Memorymentioning
confidence: 96%
See 2 more Smart Citations